The Effect of Outdoor Education Activities at SMK Negeri 2 Semarang on Physical Education Instruction to Enhance Student Motivation - Janu Setyawan; Ibnu Fatkhu Royana; Muh Isna Nurdin Wibisana (LPPM Universitas PGRI Semarang, 2026)
This study aims to determine the effect of outdoor education activities on students learning motivation in Physical Education, Sports, and Health (PJOK) classes at SMK Negeri 2 Semarang. The background of this study is based on the low level of students learning motivation, as evidenced by a lack of active participation, enthusiasm, and engagement in PJOK classes, which are still dominated by conventional methods. This study employed a quantitative method with a quasi-experimental design, specifically a pretest-posttest control group design. The sample consisted of two groups: an experimental group that received outdoor education and a control group that used conventional teaching methods. Data were collected using a learning motivation questionnaire, and statistical analysis was conducted using a paired-sample t-test and a test for differences between groups.The results of the study indicate that there was a significant increase in learning motivation in the experimental group, with a significance level of 0.004 (p < 0.05), whereas no significant increase was observed in the control group (p > 0.05). This suggests that outdoor education activities have a positive effect on students learning motivation. Outdoor-based learning creates a more engaging and challenging learning environment and increases students active participation.Thus, it can be concluded that outdoor education is an effective alternative learning strategy for enhancing students motivation in physical education classes. It is hoped that this study will serve as a reference for teachers in developing innovative and context-based teaching methods.